Confess: Menjelajahi maraknya Confeesion Online di kalangan remaja di era digital dan implikasi psikologisnya - Natasya Aprilia; Lukman Hakim (LP2M Universitas Sarjanawiyata Tamansiswa, 2025)
TikTok's growth has dramatically altered the terrain of teenage social interaction, establishing a one-of-a-kind platform for self-expression and peer participation. This study investigates the problem of adolescent confessions via the TikTok platform, focussing on how the app may be used to share personal experiences and feelings. Furthermore, the researcher want to investigate the influence of someone confessing or declaring their sentiments first to a loved one. Using a qualitative method, this study examines several TikTok patterns for Confess activities that encourage viewers to expose sensitive elements of their life, typically in the name of amusement or humour. According to the findings, TikTok activities are not only promotes a sense of community and belonging among teenagers, but it also influences their self-esteem and identity construction. Confession allows individuals to manage their weaknesses, seeking approval and support from their friends while dealing with societal pressures. According to analysis, confessing can have both beneficial and bad implications, including anxiety caused by public attention. This study contributes to a better understanding of how digital platforms impact teenage behaviour and mental health in today's world by investigating the dual nature of confessing on TikTok. Confession, on the other hand, can give direct emotional experiences in the form of rejection and acceptance, which can have a considerable impact on people' well-being, with a wide variety of effects ranging from mild to major.